Immunohistochemical expression of vitamin D receptor in melanocytic naevi and cutaneous melanoma: a case–control study. (1st July 2018) - del Puerto, C.; Navarrete‐Dechent, C.; Molgó, M.; Camargo, C.A.; Borzutzky, A.; González, S.
Summary: Background: Vitamin D deficiency is associated with higher risk of cancer, possibly due to its antiproliferative, antiangiogenic, proapoptotic, cell‐differentiating and anti‐invasive effects. The anticarcinogenic role of vitamin D in melanoma is still a matter of debate. Loss of nuclear and cytoplasmic vitamin D receptor (VDR) expression in melanoma cells has been reported. Objectives: To analyse VDR immunohistochemical expression in benign dermal naevi (DN) and malignant melanoma (MM). Methods: A case–control study evaluated nuclear and cytoplasmic VDR immunohistochemical staining in 54 DN and 55 MM tissue samples. Results: There was significantly higher cytoplasmic VDR positivity in DN compared with MM (59% vs. 16%, P < 0·001). The mean VDR cytoplasmic expression was also higher in DN vs. MM ( P < 0·001). No differences in nuclear VDR positivity were observed between groups, but mean nuclear VDR expression was significantly lower in DN vs. MM ( P = 0·02). The loss of cytoplasmic VDR in MM was associated with Clark level, tumour staging and American Joint Committee on Cancer pTNM staging ( P =0·004, 0·009 and 0·02, respectively). Conclusions: Alterations in VDR expression and localization are found in MM compared with DN. Loss of cytoplasmic VDR was associated with melanoma tumour size, suggesting that loss of cytoplasmic VDR may be a prognostic factor.